1285 Reporting of Robotic Pancreaticoduodenectomy As A Surgical Innovation: Systematic Review and Narrative Synthesis. (12th October 2021) - Scroggie, D; Lee, K S; Purves, R; Sewart, E; Van Laarhoven, S; Robinson, T; Rees, J; Pathak, S
Abstract: Aim: Pancreaticoduodenectomy (PD) is most commonly performed using open surgical techniques. Minimal access approaches have reduced the morbidity of many types of surgery, however technical limitations have hindered the widespread adoption of laparoscopic methods for PD. There has been increasing use of surgical robots to facilitate a minimal access approach, motivated by improved visualisation, ergonomics and dexterity compared to standard laparoscopic methods. Methods for the safe introduction of novel techniques are lacking, and the way in which surgical innovations are reported may affect adoption into clinical practice. The aim of this study is to understand how robotic PD has been reported as a surgical innovation. Method: A systematic review is being conducted by the trainee led RoboSurg Collaborative. A literature search was performed to identify primary research reporting outcomes of robotic PD. Articles are being screened in duplicate by title and abstract, then by full text review. The following data will be extracted: study methodology and rationale; centre, surgeons and patient details; governance and ethical considerations; learning curves; details of the intervention, including modifications; and how outcomes were reported, including use of core outcome sets. The data will be analysed using a narrative synthesis method. Results: The search identified 1305 articles reporting on robotic pancreas surgery. An interim report of progress will be presented. Conclusions: A rich narrative synthesis will enable innovators to understand how robotic PD has been reported. This will encourage transparent, methodical, and meaningful reporting of robotic PD, increasing the quality of clinical evidence.